3D bioprinted organ‐on‐chips. Issue 1 (1st May 2022) - Rahmani Dabbagh, Sajjad; Rezapour Sarabi, Misagh; Birtek, Mehmet Tugrul; Mustafaoglu, Nur; Zhang, Yu Shrike; Tasoglu, Savas
Abstract: Organ‐on‐a‐chip (OOC) platforms recapitulate human in vivo‐like conditions more realistically compared to many animal models and conventional two‐dimensional cell cultures. OOC setups benefit from continuous perfusion of cell cultures through microfluidic channels, which promotes cell viability and activities. Moreover, microfluidic chips allow the integration of biosensors for real‐time monitoring and analysis of cell interactions and responses to administered drugs. Three‐dimensional (3D) bioprinting enables the fabrication of multicell OOC platforms with sophisticated 3D structures that more closely mimic human tissues. 3D‐bioprinted OOC platforms are promising tools for understanding the functions of organs, disruptive influences of diseases on organ functionality, and screening the efficacy as well as toxicity of drugs on organs. Here, common 3D bioprinting techniques, advantages, and limitations of each method are reviewed. Additionally, recent advances, applications, and potentials of 3D‐bioprinted OOC platforms for emulating various human organs are presented. Last, current challenges and future perspectives of OOC platforms are discussed. Abstract : Organ‐on‐chip platforms have the potential to revolutionize personalized therapies by a more realistic recapitulation of human organs in vitro, enabling the study of therapeutical outcomes and conceivable adverse side‐effects of administered medicine. Integration of 3D bioprinting with organ‐on‐chip technologies can facilitate the fabrication of 3D multicellular chips with rapid turn‐around time for researchers with limited microfabrication knowledge.